The Influence of Financial Literacy, Financial Technology, and Hedonistic Lifestyle on Gen Z’s Financial Behavior - Megia Yarifuni; Felisia Ayuningtyas Marhanani (JRSI (Jurnal Rekayasa Sistem dan Industri), 2025)
A person's social status is determined, in part, by their lifestyle. Many people prioritize their appearance and the items they use to demonstrate their social status. This trend has also given rise to financial technology systems to facilitate shopping for goods and other necessities. Lifestyle and the use of financial technology, if not balanced with adequate financial literacy, will lead someone into poverty. This study aims to determine the influence of financial literacy, financial technology, and a hedonistic lifestyle on the financial behavior of Generation Z. The data collected were primary data obtained through questionnaires. This study was quantitative, using statistical data processing. The hypotheses were tested using SmartPLS. The results indicate that financial literacy, financial technology, and a hedonistic lifestyle have a positive influence on the financial behavior of Generation Z